Dictionary milk, Milch, lait, leche four language dictionary dairy products ; English-German-French-Spanish - Schneider, Christoph; Schmandke, Horst 1935-2021; Poulnot, André (Behr, 1995)
A dictionary of dairying and dairy products terminology in four languages, English, German, French and Spanish.
Keywords: Zuivelproducten; Dairy products -- Dictionaries -- Polyglot; Milk -- Dictionaries -- Polyglot; Milch; Milchprodukt; Mehrsprachiges Wörterbuch; Wörterbuch